Outcomes among pediatric patients with cancer who are treated on trial versus off trial: A matched cohort study. Issue 15 (26th May 2020) - Schapira, Marilyn M.; Stevens, Evelyn M.; Sharpe, James E.; Hochman, Lauren; Reiter, Joseph G.; Calhoun, Shawna R.; Shah, Shivani A.; Bailey, Leonard Charles; Bagatell, Rochelle; Silber, Jeffrey H.; Tai, Eric; Barakat, Lamia P.
Abstract : Background: Approximately 50% of children with cancer in the United States who are aged <15 years receive primary treatment on a therapeutic clinical trial. To the authors' knowledge, it remains unknown whether trial enrollment has a clinical benefit compared with the best alternative standard therapy and/or off trial (ie, clinical trial effect). The authors conducted a retrospective matched cohort study to compare the morbidity and mortality of pediatric patients with cancer who are treated on a phase 3 clinical trial compared with those receiving standard therapy and/or off trial. Methods: Subjects were aged birth to 19 years; were diagnosed between 2000 and 2010 with acute lymphocytic leukemia (ALL), acute myeloid leukemia (AML), rhabdomyosarcoma, or neuroblastoma; and had received initial treatment at the Children's Hospital of Philadelphia. On‐trial and off‐trial subjects were matched based on age, race, ethnicity, a diagnosis of Down syndrome (for patients with ALL or AML), prognostic risk level, date of diagnosis, and tumor type. Results: A total of 428 participants were matched in 214 pairs (152 pairs for ALL, 24 pairs for AML, 32 pairs for rhabdomyosarcoma, and 6 pairs for neuroblastoma). The 5‐year survival rate did not differ between those treated on trial versus those treated with standard therapy and/or off trial (86.9% vs 82.2%; P = .093). On‐trial patients had a 32% lower odds of having worse (higher) mortality‐morbidity composite scores, although this did not reach statistical significance (odds ratio, 0.68; 95% confidence interval, 0.45‐1.03 [ P = .070]). Conclusions: There was no statistically significant difference in outcomes noted between those patients treated on trial and those treated with standard therapy and/or off trial. However, in partial support of the clinical trial effect, the results of the current study indicate a trend toward more favorable outcomes in children treated on trial compared with those treated with standard therapy and/or off trial. These findings can support decision making regarding enrollment in pediatric phase 3 clinical trials. Abstract : The current study compares mortality and late effects among pediatric patients with cancer who are treated on trial versus standard therapy and/or off trial using a matched cohort design among 428 participants with acute lymphocytic leukemia, acute myeloid leukemia, rhabdomyosarcoma, or neuroblastoma. The authors report no statistically significant difference in outcomes, a finding that can support decision making regarding enrollment in pediatric phase 3 trials.